The effects of office bleaching techniques on nanoceramic composite resin - CİMİLLİ, ZÜHRE HALE (My University, 2023)
Objective: The aim was to evaluate the effect of activated bleaching agents on the nanoceramic composite resins based on microhardness and Methods: Opalescence Boost (Ultradent Products, USA) and Whiteness HP Blue Calcium (FGM Dental Products, Brazil) bleaching agents and a nanoceramic composite resin Ceram.X (R) SphereTECTM One (DENTSPLY, Germany) were used in the study. Fifty composite samples in disc form (8x2mm) were prepared. The samples were polished with discs (Sof-Lex, 3M Dental Products, St.Paul, USA) and incubated in the dark in distilled water. Samples were divided into 5 main groups (n=10). Control group (C), Opalescence Boost/ without light (OB), Opalescence Boost/ with light (VHN) measurements were conducted after the bleaching process. Statistical analyses were performed using the Kruskal Wallis - H test and the Mann Whitney - U test; a p value of < 0.05 was considered statistically significant. Result: The VHN was significantly different among groups in terms of the application of bleaching agents and light (p = 0.008). The Ra was not significantly different among groups with respect to the application of bleaching agents or lighting conditions (p = 0.144). Conclusion: Within the conditions of this study, after bleaching procedure the microhardness values of the nanoceramic composite increased, however bleaching did not show any effect on surface roughness.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Bleaching; composite resin; microhardness; surface roughness; RESTORATIVE MATERIALS; SURFACE-ROUGHNESS; MICROHARDNESS; LIGHT; PEROXIDE; HARDNESS; GELS; Bleaching; composite resin; microhardness; surface roughness